2020
DOI: 10.3390/ijms21186957
|View full text |Cite
|
Sign up to set email alerts
|

HSPA1L Enhances Cancer Stem Cell-Like Properties by Activating IGF1Rβ and Regulating β-Catenin Transcription

Abstract: Studies have shown that cancer stem cells (CSCs) are involved in resistance and metastasis of cancer; thus, therapies targeting CSCs have been proposed. Here, we report that heat shock 70-kDa protein 1-like (HSPA1L) is partly involved in enhancing epithelial–mesenchymal transition (EMT) and CSC-like properties in non-small cell lung cancer (NSCLC) cells. Aldehyde dehydrogenase 1 (ALDH1) is considered a CSC marker in some lung cancers. Here, we analyzed transcriptional changes in genes between ALDH1high and ALD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Similar fibronectin adsorption amounts and supraphysiologically high stiffness (30–50 MPa) than pre‐mineralized extracellular matrix were detected in ISB‐P and PCL (Figure S14), reinforcing the involvement of biological factors, here Hsp1a‐induced integrin α5 and αν functional activity, in enhancing stem cell adhesion on ISB‐P 86 . Taken together, these results revealed that the integrin α5 and αν subunit functions as major surface receptors for ISB‐P in stem cells possibly by the activation of Hspa1a in a special biological signaling pathway, 87–89 not by physical factors such as surface roughness and adhesive protein adsorption. Further study is necessary to investigate whether the activation of Hspa1a genes by ISB‐P to regulate cell adhesion is unique among PU‐PCL shape‐memory polymers and what are the key chemical structures to tune Hspa1a genes.…”
Section: Resultssupporting
confidence: 65%
“…Similar fibronectin adsorption amounts and supraphysiologically high stiffness (30–50 MPa) than pre‐mineralized extracellular matrix were detected in ISB‐P and PCL (Figure S14), reinforcing the involvement of biological factors, here Hsp1a‐induced integrin α5 and αν functional activity, in enhancing stem cell adhesion on ISB‐P 86 . Taken together, these results revealed that the integrin α5 and αν subunit functions as major surface receptors for ISB‐P in stem cells possibly by the activation of Hspa1a in a special biological signaling pathway, 87–89 not by physical factors such as surface roughness and adhesive protein adsorption. Further study is necessary to investigate whether the activation of Hspa1a genes by ISB‐P to regulate cell adhesion is unique among PU‐PCL shape‐memory polymers and what are the key chemical structures to tune Hspa1a genes.…”
Section: Resultssupporting
confidence: 65%
“…Amongst these, a protein that is overexpressed together with a stem cell marker protein is classified as a CSC marker protein (32). In previous experiments, ALDH1 was used as a marker protein to classify overexpressed genes in LCSCs (33). Through classification using the feature extraction software, information on 4,300 genes that were expressed >2x higher in ALDH1 + cells than in the control group was obtained (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating data indicated that HSP70 family can play a causal role in cancer initiation. Evidence showed that HSPA1L can enhance cancer stem cell-like properties via regulating β-Catenin transcription and activating IGF1Rβ [ 25 ]. RNF144A interacted with HSPA2 can promote tumor growth and progression [ 26 ].…”
Section: Discussionmentioning
confidence: 99%